BRACHYTHERAPY ALONE OR WITH NEOADJUVANT PHOTODYNAMIC THERAPY FOR AMELANOTIC CHOROIDAL MELANOMA: Functional Outcomes and Local Tumor Control. Issue 11 (November 2016) - Blasi, Maria A.; Laguardia, Michela; Tagliaferri, Luca; Scupola, Andrea; Villano, Antonio; Caputo, Carmela G.; Pagliara, Monica M.
Abstract : Purpose: To compare visual outcomes and local tumor control between two groups of patients with amelanotic choroidal melanoma treated with brachytherapy alone, or neoadjuvant photodynamic therapy before brachytherapy. Methods: Patients diagnosed with amelanotic choroidal melanoma were recruited for the study and divided into two groups: brachytherapy alone (Group A) and photodynamic therapy preceding brachytherapy (Group B). Patients of both groups were selected to be comparable. Results: Twenty-six patients with amelanotic choroidal melanoma were enrolled in the study. Within Group B, 1 month after photodynamic therapy, ultrasonography showed reduction of tumor height in 11 patients (73.4%). The mean doses of irradiation to macula and optic nerve, at baseline were 74.37 and 52.07 Gy, whereas after photodynamic therapy there was a decrease of 17.26% ( P = 0.008) and 21.22% ( P = 0.025), respectively. In terms of visual acuity, a mean decrease of 14 ETDRS letters and 5 ETDRS letters was observed at 24 months follow-up, in Groups A and B, respectively ( P = 0.001). Conclusion: Photodynamic therapy as neoadjuvant therapy before brachytherapy reduces tumor thickness in 73.4% of cases. As a result, a decrease of radiation toxic effects on visual function could be obtained, without compromising disease control. Abstract : Supplemental Digital Content is Available in the Text.Photodynamic therapy used before brachytherapy, for amelanotic uveal melanomas, might reduce tumor thickness, and consequently the radiation dose to the macula and optic disk, thus decreasing the incidence of radiation-induced toxicity, and without compromising the disease control.